Marketing Mix Strategy in Bojong Karnival Tourism Attraction for Increasing Visiting Interest - Suci Ramadhanti; Rizki Nurul Nugraha (West Science Social and Humanities Studies, 2024)
This research aims to analyze the Marketing Mix at the Bojong Karnival tourist attraction to increase Visiting Interest. This research data uses primary and secondary data. The data analysis technique uses SWOT analysis with the IFAS and EFAS matrices. The results of this study show that the identified marketing mix on Bojong Carnival tourist attractions has been implemented. Marketing mix that has been implemented are products, prices, places, promotions, physical evidence, people, and processes. The IFAS Matrix shows a scor 3,06 from the total strength-weakness factors, while the EFAS Matrix shows score 2,92 from the total opportunity-challenge factors. The scors from the IFAS Matrix is used as the x and the value from the EFAS Matrix is used as the y in the IE Matrix which shows the marketing mix of Bojong Karnival located in cell IV, described as Growth and Build. SWOC matrix shows that Bojong Karnival's position is in Quadrant 1, which means it is in a strong position and has opportunities. The Strength, Weakness, Opportunity, and Challenge matrix is used as a tool to create a development model for marketing mix strategies by looking at 4 alternative strategies, SO Strategy, WO Strategy, SC Strategy, and WC Strategy to increasing interest visiting in Bojong Karnival.